'Proceeding like Guy Faux': the Antiquarian Investigation of St Stephen's Chapel Westminster, 1790–1837. (19th October 2016) - Hill, Rosemary
Abstract: St Stephen's Chapel Westminster is one of Europe's great lost buildings. An elaborate palatine chapel, work on it began in 1292 and continued until at least 1363. After 1546 it became the House of Commons and was so obscured by successive alterations that the original building had passed out of living memory by the late eighteenth century. It was then that it attracted the interest of a number of antiquaries who recorded it in the years up to and after the fire of 1834. In 1837 it was demolished. The antiquaries' accounts provide the only records of the chapel's appearance and construction and have been much used in studies of the medieval building. This article, however, considers them as a body of work in their own right, one that casts light not only on St Stephen's but on the changing attitudes of the Romantic age towards history and the medieval past in the years which saw the transformation of the Gothic Revival and the birth of the modern idea of conservation.